(untitled) (Research, Society and Development, 2021)
The knowledge of the quantity and composition of the deposited biomass is useful to plan the nutrient management of cultivations in agroforestry systems. The objective of this work was to evaluate the production of biomass and litter in two agroforestry systems with organic and conventional cultivations of sour orange. The areas use models of orange production by monoculture and under agroforestry systems: the first agroforestry system is composed of rows of brazilian mahogany (Swietenia macrophylla K.) accompanied by double rows of orange trees (Citrus aurantium L.); the second system is composed of rows of ingá (Ingá edulis Mart.) accompanied by double rows of orange trees. A completely randomized design was used in a 10x2 factorial scheme, with 4 replications. The locations within the management systems were organized as follows: agroforestry system composed of mahogany trees; Ingá trees agroforestry system; conventional sour orange monoculture system. The areas that the biomass and litter were collected in the locations in the systems were: between plants in the row for cultivation of forest species that make up the system; between rows of the forest species row and orange cultivation row; between plants in the orange cultivation row; between rows of the double row of orange cultivation. Two periods were analyzed in the experiment: the months of lowest and highest rainfall. Agroforestry systems promoted greater biomass and litter to the soil compared to monoculture. In this way, they were configured as a beneficial practice for the soil in sour orange crops in the Brazilian Amazon.